Pro-dermcidin and derivatives as potential therapeutics for lethal experimental sepsis - Chen, Weiqiang; Qiang, Xiaoling; Zhu, Cassie Shu; Li, Jianhua; Lou, Li; Wang, Ping; Tracey, Kevin J.; Wang, Haichao (Frontiers in Immunology, 2025)
A 110-amino acid precursor of dermcidin (pre-dermcidin, pre-DCD) with a 19-residue N-terminal leader signal sequence can be secreted by human eccrine sweat glands as a leader-less pro-domain-containing peptide (pro-DCD), which is enzymatically cleaved to generate C-terminal anti-microbial peptides (dermcidin-1, DCD-1) capable of killing various bacteria. Previously, it was unknown whether pro-DCD could be pharmacologically developed as potential therapeutics for lethal sepsis. Here, we demonstrated that pharmacological suppression of pro-DCD with polyclonal antibodies worsened sepsis-induced inflammation and liver injury, whereas supplementation of pro-DCD or its PEGylation derivatives significantly protected against sepsis, even when given 2–24 h after disease onset. These protective effects were associated with a significant reduction in circulating levels of surrogate biomarkers [e.g., Granulocyte Colony Stimulating Factor (G-CSF), Interleukin-6 (IL-6), keratinocytes-derived chemokine (KC), Monocyte Chemoattractant Protein 1 (MCP-1), Macrophage Inflammatory Protein-2 (MIP-2), and Soluble Tumor Necrosis Factor Receptor I (sTNFRI)], tissue injury, and blood bacterial counts. Although pro-DCD or its PEGylation derivatives failed to directly kill bacteria across a wide range of concentrations, they were able to activate microtubule-associated protein 1A/1B-light chain 3 (LC3), a marker of autophagy and phagosome maturation in LC3-associated bacterial phagocytosis. Our findings suggest that pro-DCD-derived agents hold promise as potential therapies for clinical sepsis.